Before Jim Crow : The Politics of Race in Postemancipation Virginia - Dailey, Jane Elizabeth, 1963- (Book collections on Project MUSE., 2000)
Long before the Montgomery bus boycott ushered in the modern civil rights movement, black and white southerners struggled to forge interracial democracy in America. This book examines the most successful interracial coalition in the 19th-century South, Virginia's Readjuster Party, and uncovers a surprising degree of fluidity in postemancipation southern politics. Melding social, cultural, and political history, the author chronicles the Readjusters' efforts to foster political cooperation across the colour line.